The Maidan Massacre in Ukraine: The Mass Killing that Changed the World - Katchanovski, Ivan (Rethinking Political Violence, 2024)
This open access book provides a comprehensive analysis of the Maidan massacre in Ukraine. It uses a theoretical framework of rational choice, moral hazard, state- repression backfire, and Weberian ideas about rational action to explore the massacre. The book draws on publicly available videos, photos and audio recordings of the massacre in English, Ukrainian, Russian, Polish and other languages, along with several hundred individual testimonies and revelations from the Ukrainian investigation and a trial and its verdict. By examining which parties were responsible for the massacre, the book analyses its implications for not only Russia’s war on Ukraine but also political developments across the globe